PERANCANGAN USULAN HARGA JUAL BARU UNTUK MENU-MENU PADA PAYANGKA RESTO 77 DENGAN BERBASIS ESTIMASI BIAYA - Louis, Jason
This research aims to design a proposal for new selling prices for the menus offered by Payangka Resto 77. The formulation of these new prices is motivated by the restaurant's declining profits despite increased sales, which has made it challenging to achieve the profit targets set by the restaurant management. This decrease in profit is due to rising restaurant costs without a corresponding increase in menu prices. The restaurant management has been unable to raise prices as they lack detailed knowledge of the specific costs associated with each menu item, preventing them from determining prices that could increase profits without burdening customers.